Comparison of Techno-Economic Solutions for 5G Networks and Beyond - Christos Bouras; Fotios Kaisoudis; Anastasia Kollia (The Seventeenth International Conference on Wireless and Mobile Communications (ICWMC 2021), July 18 – 22, 2021, Nice, France, 2021)
The fifth-generation (5G) envisions a society that is constantly interconnected with a large number of devices, anywhere and anytime. The developed technologies play a substantial role, allowing low latency, large volumes of data traffic, and improved Quality of Service (QoS). The advent of 5G encourages providers and investors to develop innovative services that meet consumer demands. However, the viability of a new service should be investigated from an economic perspective. Therefore, the introduction of effective techniques concerning the financial evaluation of such services is essential. This paper analyzes 5G technologies and evaluates them in a techno-economic point of view using pricing models. In particular, the main factors used to estimate the different types of costs are Capital Expenditures (CAPEX) and Operational Expenditures (OPEX), which define the viability of each investment. Based on the results obtained, 5G is a profitable investment due to its low cost and increase in the average data consumption of each consumer. Finally, using metrics, it is found that reusing existing sites is less costly than to develop a dense macro-cell network.